2017
DOI: 10.3892/ijo.2017.4024
|View full text |Cite
|
Sign up to set email alerts
|

Secretomic profiling of cells from hollow fiber bioreactor reveals PSMA3 as a potential cholangiocarcinoma biomarker

Abstract: Cholangiocarcinoma (CCA), derived from the bile duct, occurs with a relatively high incidence in Northeast Thailand. Early diagnosis is still hampered by the lack of sufficient biomarkers. In recent years, biomarker discovery using secretomes has provided interesting results, including our studies on CCA secretomes, especially with three-dimensional cell cultures. Thus, cells cultured using the hollow fiber bioreactor (HFB) with 20 kDa molecular weight cut-off (MWCO) yielded higher quality and quantity of secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…PSMA3 , alternatively known as proteasome subunit alpha type 3, encodes the α7 subunit, which makes up the outer ring of the 20S core particle. Cancer-related reports on the relation of PSMA3 expression and malignancy are limited, including metastatic gastric cancer and cholangiocarcinoma [ 82 , 83 ]. PSMA4 , alternatively known as proteasome subunit alpha type 4, encodes the α3 subunit, which makes up the outer ring of the 20S core particle.…”
Section: Discussionmentioning
confidence: 99%
“…PSMA3 , alternatively known as proteasome subunit alpha type 3, encodes the α7 subunit, which makes up the outer ring of the 20S core particle. Cancer-related reports on the relation of PSMA3 expression and malignancy are limited, including metastatic gastric cancer and cholangiocarcinoma [ 82 , 83 ]. PSMA4 , alternatively known as proteasome subunit alpha type 4, encodes the α3 subunit, which makes up the outer ring of the 20S core particle.…”
Section: Discussionmentioning
confidence: 99%
“…Proteasome-related genes play key roles in the formation of proteasomal structures and in maintaining its activity. Recent studies have revealed that some proteasome-related genes, such as PSMA3 and PSMC2, can promote the progression of malignant biliary tumors and act as potential biomarkers to predict prognosis ( Verathamjamras et al, 2017 ; Duan et al, 2021 ; Zhu et al, 2021 ). To fully explore the function of the proteasome in the progression of iCCA, 43 proteasome-related genes were included, and the hierarchical heatmap showed that these genes, such as PSMD1, PSMB4, PSMD13, and PSMC4, were out of balance during trajectory development ( Figure 2G ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, several studies have demonstrated the abnormal expression profiles of PSMA3 in several cancers and identified PSMA3 as a cancer-related indicator [11]. An analysis of plasma samples from normal individuals, cholangiocarcinoma (CCA) patients, and hepatocellular carcinoma patients was conducted by Verathamjamras et al [12], and the results provided evidence that PSMA3 could be a potential biomarker for CCA. Also, Ding et al reported that PSMA3 was explicitly enriched in the serum of patients with metastatic gastric cancer [13].…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of plasma samples from normal individuals, cholangiocarcinoma (CCA) patients, and hepatocellular carcinoma patients was conducted by Verathamjamras et al. [12], and the results provided evidence that PSMA3 could be a potential biomarker for CCA. Also, Ding et al.…”
Section: Introductionmentioning
confidence: 99%